Redescription and commentary on the Chinese mayfly Vietnamella sinensis (Ephemeroptera: Vietnamellidae) - Hu, Ze; Ma, Zhen-Xing; Luo, Juan-Yan; Zhou, Chang-Fa (Zootaxa, 2017)
The genus Vietnamella Tshernova, 1972 is reviewed and 3 valid species are confirmed. They are V. ornata (Tshernova, 1972), V. sinensis (Hsu, 1936) (=V. dabieshanensis You & Su, 1987, new synonym; =V. qingyuanensis Zhou & Su, 1995, new synonym; =V. guadunensis Zhou & Su, 1995, new synonym) and V. thani Tshernova, 1972. The nymphal and key imaginal characters of V. sinensis are described and figured. The monogeneric family Vietnamellidae has long series of autapomorphies (two pairs of projections on head, modified mandibles, slender maxillae with few setae, round hindwings, and half of egg covered with single cap) and some plesiomorphies (seven pairs of gills, large hindwings, few marginal intercalaries on forewings). The structures of mouthparts, head and forefemora suggest that nymphs of Vietnamella may be able to move substrates and scrape food from them. Morphological evidences show that the family Vietnamellidae is a basal clade of Ephemerelloidea.